A highly efficient heterogeneous copper-catalyzed Chan-Lam coupling between thiols and arylboronic acids leading to diaryl sulfides under mild conditions. Issue 23 (9th June 2016) - Lin, Yang; Cai, Mingzhong; Fang, Zhiqiang; Zhao, Hong
Abstract: The heterogeneous Chan-Lam coupling reaction between thiols and arylboronic acids was achieved in EtOH at room temperature in the presence of 5 mol % of MCM-41-immobilized 1, 10-phenanthroline-copper(II) complex [MCM-41-1, 10-Phen-CuSO4 ] with n -Bu4 NOH (40% aq) as base under O2 atmosphere, yielding a variety of unsymmetrical diaryl sulfides in good to excellent yields under mild and green conditions. The new heterogeneous copper complex can easily be prepared by a simple procedure from commercially readily available and inexpensive reagents, and recovered by a simple filtration of the reaction solution and recycled for at least eight times without significant loss of catalytic activity. Graphical abstract: